2009
DOI: 10.4161/cbt.8.24.10131
|View full text |Cite
|
Sign up to set email alerts
|

Targeting HER2 signaling pathway for radiosensitization: Alternative strategy for therapeutic resistance

Abstract: Several studies have indicated the potential value of targeting HER-2 signaling to enhance the anti-tumor activity of ionizing radiation. However, therapeutic resistance resulting from several factors, including activation of the downstream pathway, represents a major obstacle to treatment. Here, we investigated whether inhibitors targeting downstream of HER-2 signaling would radiosensitize SKBR3 breast cancer cells that exhibit overamplification of HER2. Selective inhibition of MEK-ERK signaling using pharmac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
22
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 29 publications
(32 reference statements)
4
22
0
Order By: Relevance
“…We previously showed that inhibition of AKT1 using RNAi increased radiosensitivity of EGFR-or Ras-activated cell lines (Kim et al, 2005) and the other study showed that AKT inhibitor (API) or AKT1 siRNA inhibited repair of DNA double strand breaks (DSBs) in EGFR-activated lung cancer cell lines as measured by the γH2AX foci assay (Toulany et al, 2008). SKBR3 breast cancer cells having activated HER-2 signaling also showed similar findings ( Figure 3, No et al, 2009). …”
Section: Targeting Aktsupporting
confidence: 60%
“…We previously showed that inhibition of AKT1 using RNAi increased radiosensitivity of EGFR-or Ras-activated cell lines (Kim et al, 2005) and the other study showed that AKT inhibitor (API) or AKT1 siRNA inhibited repair of DNA double strand breaks (DSBs) in EGFR-activated lung cancer cell lines as measured by the γH2AX foci assay (Toulany et al, 2008). SKBR3 breast cancer cells having activated HER-2 signaling also showed similar findings ( Figure 3, No et al, 2009). …”
Section: Targeting Aktsupporting
confidence: 60%
“…Previous research indicated that targeting of PI3K-AKT-mTOR signaling significantly radiosensitized HER2-activated breast cancer cells by inhibition of DNA repair. Therefore, blocking the PI3K-AKT-mTOR pathway may help patients to overcome resistance to currently available HER2 inhibitors plus irradiation [30].…”
Section: Discussionmentioning
confidence: 99%
“…This subtype may be relatively resistant to post-lumpectomy RT [14]. Preclinical studies have shown that EGFR expression and activation by ligands correlate with radioresistance and that signal transduction initiated by receptor activation promotes cancer cell survival and proliferation after ionizing radiation [27][28][29][30]. HER2 inhibitors can affect cellular responses to ionizing radiation by induction of apoptosis and cell cycle arrest and by impeding DNA repair [27,31].…”
Section: Discussionmentioning
confidence: 99%
“…Toulany and colleagues (26) reported that radiation, but not EGF, enhances EGFR/HER2 heterodimerization and activates the downstream Akt signaling pathway. Given that HER2 is a prognostic factor of bladder cancer progression (27,28), some may wonder whether HER2 inhibition itself accounts for the difference in radiosensitizing activity (29,30) between afatinib and erlotinib. Our results in Fig.…”
Section: Discussionmentioning
confidence: 99%